Large–scale avulsion of the late Quaternary Sutlej river in the NW Indo–Gangetic foreland basin - Singh,A; Gupta,S; Sinha,R; Carter,A; Kristina,KJ; Mark,DF; Buylaert,J-P; Mason,PJ; Murray,AS; Jain,M; Paul,D (2015)
River avulsions are important processes in the spatial evolution of river systems in tectonically active sedimentary basins as they govern large–scale patterns of sediment routing. However, the pattern and timing of avulsions in large river systems are poorly documented and not well understood. Here we document late Quaternary paleo– river channel changes in the Indo–Gangetic basin of northwest India. Using a combination of satellite remote sensing and detailed sediment coring, we analyse the large–scale planform geometry, and detailed sedimentary andstratigraphic nature of a major fluvial sedimentary deposit in the shallow subsurface. This sediment body records aggradation of multiple fluvial channel fills. Satellite remote sensing analysis indicates the trace of the buried channel complex and demonstrates that it exists in region of the Himalayan foreland where no major rivers are currently present. Thus it records the former drainage pathway of a major river, which has since been diverted. We use optically stimulated luminescence dating techniques to develop an age model for the stratigraphic succession and hence constrain the timing of river channel existence and diversion. Provenance analysis based on U–Pb dating of detrital zircons and detrital mica Ar–Ar ages indicate sediment sources in the Higher Himalayan Crystalline andLesser Himalayan Crystalline Series indicating that this paleo–river channel system formed a major perennial river derived from the main body of the Himalaya. Specifically we are able to fingerprint bedrock sources in thecatchment of the present–day Sutlej river indicating that the paleo–fluvial system represents the former course of the Sutlej river prior to a major nodal avulsion to its present day course. Our results indicate that on geologically relatively short time–scales, we observe dramatic along strike shifts in the location of major Himalayan rivers. Our sediment records